Comportamentos éticos/ morais: em foco a produção de artigos da Análise do Comportamento compreendida entre os anos de 2002 a 2015 - Zaclis, Claudia Sartori (2016)
The purpose of this study was to discuss the national production and the Behavior Analysis production, in the form of articles published in journals available online from 2002 to 2015, about ethical/moral behavior. We also observed studies with the following behavioral classes: politeness, respect, empathy and cooperation. The search and selection process involving articles in BVSPsi, PePsic and SciELO databases occurred in four stages: 1) Initial survey; 2) Article selection; 3) Article categorization; 4) Identification and categorization of articles written about Behavior Analysis. Initially we presented general results considering all approaches and later the results of the articles about Behavior Analysis. In our general survey, we selected 87 articles: the prevailing area of knowledge of publications was Psychology, the theoretical approach with most mentions was Cognitivism, the prevailing research type was Theoretical Conceptual approach. There was at least one article for each theme (politeness, respect, cooperation and empathy). In regard to Behavior Analysis, we found 19 articles, and most of them addressed the theme as Ethics (rather than Moral). The prevailing research type was Theoretical Conceptual approach, and we identified papers addressing behaviors of politeness, respect and empathy, but the cooperation theme was not addressed. It is evident, therefore, that the ethical theme should be subjected to more studies on the part of behavior analysts. We suggest that future studies should not be only be conceptual or descriptive, but also propose interventions with a view to bringing new understanding, discoveries and mainly changes in our activity in relation to social matters involving ethical/moral behaviors